The effect of gamma irradiation on selected growth factors and receptors mRNA in glycerol cryopreserved human amniotic membrane - Mat Yatim, Rusidah (2015)
Human amniotic membrane (HAM), due to its high biocompatibility, low immunogenicity, anti-microbial, anti-viral properties as well as the presence of its growth factors, has been used in various clinical applications. These growth factors are key factors in regulating many cellular processes such as cellular growth, proliferation and cellular differentiation. The current study aimed to explore the effect of glycerol cryopreservation and gamma irradiation on the selected growth factors and receptors mRNA present in HAM. Eight growth factors, namely, EGF, HGF, KGF, TGF-α, TGF-β1, TGF-β2, TGF-β3 and bFGF and two growth factor receptors, HGFR and KGFR were evaluated in this study. The total RNA was extracted and converted to complimentary DNA using commercial kits. Subsequently, the mRNA expressions of these growth factors were evaluated using quantitative PCR and the results were statistically analyzed using REST-MCS software. This study indicated the presence of these growth factors and receptors mRNA in fresh, glycerol cryopreserved and irradiated glycerol cryopreserved HAM. In glycerol cryopreserved HAM, the mRNA expression showed up-regulation of HGF and bFGF and down-regulation of the rest of 8 genes which were EGF, HGFR, KGF, KGFR, TGF-α, TGF-β1, TGF-β2 and TGF-β3. Interestingly, the glycerol cryopreserved HAM radiated with 15 kGy showed up-regulation in the mRNA expression of 7 genes, namely, EGF, HGF, KGF, KGFR, TGF-β1, TGF-β2 and TGF-β3 and down-regulated mRNA expression of HGFR, TGF-α and bFGF. However, these mRNA expressions did not show a statistically significant difference compared to control groups. Thus, it can be concluded that the glycerol cryopreservation did not have an effect on the growth factors’ and receptors’ mRNA expression levels in HAM. Similarly, 15 kGy gamma irradiation did not have an effect on the growth factors’ and receptors’ mRNA expression in glycerol cryopreserved HAM. This finding provides a useful information to clinicians and surgeons to choose the best method for HAM preservation that could benefit patients in their treatment.